Recruitment System and Selection of Placement of Educators in the Islamic Middle School Darul Hikmah Makassar - Suriadin Suriadin (Journal of Research and Multidisciplinary, 2018)
The recruitment and placement system for teaching staff is one of the most important elements in improving the quality of education. Educators are members of the community who are devoted and appointed to support the implementation of education. Includes education unit managers, overseers, study tutors, supervisors, researchers, developers, librarians, laboratory assistants and learning resource technicians. One of the problems that often occur in the recruitment and placement of teaching staff is that the planning of recruitment is less mature so that there is often a failure in achieving school goals because a lot of work that should be done by some people must be done alone. Based on this problem, research was carried out recruitment and selection systems, placement of educators at the Darul Hikmah Islamic Middle School in Makassar. Using pure qualitative research methods. The data collection techniques, through observation and interviews. Data analysis methods are used triangulation so that data becomes more accurate. Recruitment of educators at Darul Hikmah Makassar Islamic Middle School is based on preparation and planning. The system used sequentially starts from the dissemination of information about job vacancies for the recruitment of teachers, acceptance of application files, and file selection. Furthermore, the placement of employees who are declared as graduated is based on their respective competencies and skills with an open, free, objective principle without discrimination. Placement in a position that is in accordance with the expertise, skills, talents, and abilities, while remaining in accordance with the prevailing laws and regulations.